Challenges Facing the New President in the Greater Middle East - Nada Zohdy (International Institute of Islamic Thought, 2009)
In November 2008, students, scholars, and interested citizens convened in East Lansing to hear experts speak about the Middle East. This event, “Challenges Facing the New President in the GreaterMiddle East,” was hosted by Michigan State University’s Muslim Studies Program with generous cosponsorship by the Institute for Social Policy and Understanding (ISPU) and the Association of Muslim Social Scientists of North America (AMSS). Speakers highlighted the topic’s timeliness, given the current global political climate. Experts agreed that by heeding the nuances surrounding Middle Eastern issues and contextualizing them, a positive transformation ofAmerican policy can be achieved. Professor Mohammed Ayoob (Michigan State University) articulated why the Middle East is significant: as the Muslim world’s spiritual and political heartland, understanding its politics is essential to understanding that world’s politics, and being the home ofmore than 60%of the world’s proven oil reserves and 40% of its natural gas makes it strategically important. This overview contextualized the challenges facing the Obama administration on such critical regional issues as political Islam, the Israeli-Palestinian conflict, and the Iraq War as well as the United States’ tenuous relations with Pakistan, Afghanistan, Iran, and SaudiArabia ...